2003
DOI: 10.1021/jp0302358
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Induced Association and Gelation of Aqueous Solutions of Pectin

Abstract: We report effects of oscillatory and steady shear flows on intermolecular associations and gelation in a semidilute aqueous solution of pectin in the absence and presence of a hydrogen bond breaking agent (urea). The effect of urea on the growth of intermolecular complexes stabilized through hydrogen bonds is analyzed. It is shown that when the systems are exposed to high shear rates, prominent intermolecular associative junctions emerge upon return to low shear rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…The thixotropic behaviour has been attributed to the breakdown of the network structure into smaller flocs or aggregates (Bayod et al, 2007), which decreases the viscosity of the suspension. With regard to the liquid phase, a previous investigation of model solutions of pectins has shown that while low shear rates induce gelation and shear-thickening, intense shearing may cause the disruption of intermolecular junctions leading to a decrease in viscosity (Kjøniksen, Hiorth, Roots, & Nyström, 2003). The understanding of the mechanisms of network breakage and consequent formation of flocs is relevant in the design of production processes, where the effect of prolonged shearing on the food structures should be prevented or minimised.…”
Section: Introductionmentioning
confidence: 99%
“…The thixotropic behaviour has been attributed to the breakdown of the network structure into smaller flocs or aggregates (Bayod et al, 2007), which decreases the viscosity of the suspension. With regard to the liquid phase, a previous investigation of model solutions of pectins has shown that while low shear rates induce gelation and shear-thickening, intense shearing may cause the disruption of intermolecular junctions leading to a decrease in viscosity (Kjøniksen, Hiorth, Roots, & Nyström, 2003). The understanding of the mechanisms of network breakage and consequent formation of flocs is relevant in the design of production processes, where the effect of prolonged shearing on the food structures should be prevented or minimised.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is well-known that shearing of the sample can induce or impede thermoreversible gelation. [23,24] Therefore, we performed several small-amplitude oscillatory shear experiments in the cuvette on the present system to prove this effect. In our studies [21,22] effects like different shear strains, shear history, thermal sample history and aggregation did not influence the gelation temperature of 50 8C in any case.…”
Section: Resultsmentioning
confidence: 75%
“…Generally, the n value was relevant to the physically fractal dimension, and reflected the degree of compactness of the network, and the lower values of n implied a more highly elastic gel (Gao & Nishinari, 2004;Nordby, Kjøniksen, Nyström, & Roots, 2003;Kjøniksen, Hiorth, Roots, & Nysrtom, 2003). The larger tan ı and n values at higher c NaCl in Table 1 suggested a less elastic, as a result of the screening.…”
Section: Resultsmentioning
confidence: 99%